A Simple RP?HPLC Method for the Determination of Cefdinir in Human Serum: Validation and Application in a Pharmacokinetic Study with Healthy Bangladeshi Male Volunteers (Dhaka University Journal of Pharmaceutical Sciences, 2012)
In the present study, a simple RP?HPLC method with UV detection has been validated to determine cefdinir concentrations in human serum samples and applied to determine the pharmacokinetic parameters of cefdinir in healthy Bangladeshi male volunteers. The mobile phase consisting of a mixture of 0.2 M sodium dihydrogen phosphate buffer (pH 3.2 ± 0.05 adjusted with o-phosphoric acid) and methanol at a ratio of 70:30 (v/v), was pumped at a flow rate of 1.0 ml/min through the C18 column at room temperature and the chromatographic separation was monitored at a wavelength of 254 nm with a sensitivity of 0.0001 AUFS. Cefaclor was used as internal standard. The developed method was selective and linear for cefdinir concentrations ranging from 0.05 to 5 ?g/ml for serum samples. The lower limit of quantification was defined as the lowest concentration on the calibration curve (0.05 ?g/ml) for which an acceptable accuracy of 111.60 % and a precision of 7.65 % were obtained, while the minimum detectable quantity of cefdinir was found to be 0.02 ?g/ml. The intra-day and inter-day coefficient of variation (CV) at 0.05 ?g/ml were 7.65% and 9.72%, respectively. The average recovery of cefdinir from serum was 96.43 %. Acceptable results were obtained during stability study. The mean Cmax of cefdinir was found to be 1.42 ± 0.53 ?g/ml attained at a mean Tmax of 3.81 ± 0.96 hr. The mean elimination half-life was 2.03 hours. This method proved to be simple, accurate and precise for pharmacokinetic and bioequivalence studies of cefdinir.   DOI: http://dx.doi.org/10.3329/dujps.v10i2.11790   Dhaka Univ. J. Pharm. Sci. 10(2): 109-116, 2011 (December)